PENGARUH KOMPENSASI, LINGKUNGAN PENGENDALIAN DAN KOMPETENSI PENGELOLA KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN (Survei Pada Satuan Kerja Perangkat Daerah Kabupaten Sigi) - Asbar, Andi (Katalogis, 2017)
The study is conducted in the government working units of Sigi Regency especially towards the financial administrators who preparing the financial statements in their working units. The aims of this study is to determine and analyze the influence of compensation (X1), controlling environment (X2), and competency of financial administrator (X3) on the quality of financial statements (Y), and to identify which variable that has dominant influence on the financial statements’ quality. This study expects to be beneficial in the country’s financial management and administration in accordance to the government regulations and The Ministry of Finance about financial statement. The study is descriptive quantitative that analyzed with multiple linear regression. The data used are primary and secondary data that are gathered from interviews and questionnaires distributed to 117 respondents from 42 governmental working units in Sigi Regency. The result shows that compensation, controlling environment, and competency of financial administrator simultaneously and partially have significant influence on the quality of financial statements. Of three independent variables, compensation given to and the competency of financial administrators dominantly influence the quality of financial statements in the governmental unit in Sigi Regency.